2004
DOI: 10.1108/14608790200400006
|View full text |Cite
|
Sign up to set email alerts
|

Housing people with complex needs: Finding an alternative to traditional service models

Abstract: The challenge Delayed discharge, new admissions and getting stuckDuring the initial phase of resettlement, more able residents have been among the first to move into the community, usually to group living: hostels and small group homes or core and cluster models. It is less usual to find people with their

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The quality of life for people with disability is no doubt highly related to the quality of care provided within the housing setting (Cooper et al 2005;Evans et al 2003;Fakhoury et al 2002;Kelly and Winkler 2007;Robertson et al 2005;Sergeant and Brown 2004;Tsemberis and Eisenberg 2000), but there is strong evidence to suggest that quality of life is also related to factors present within the physical care environment (Parker et al 2004). Although it is difficult to determine the causal attribution between place and care, Moos and Lemke (1980) earlier reported that the workforce who operate in well designed residential settings provide residents with more choice in their daily activities and more influence on operational policies (Parker et al 2004).…”
Section: Care and Support And Building Designmentioning
confidence: 99%
“…The quality of life for people with disability is no doubt highly related to the quality of care provided within the housing setting (Cooper et al 2005;Evans et al 2003;Fakhoury et al 2002;Kelly and Winkler 2007;Robertson et al 2005;Sergeant and Brown 2004;Tsemberis and Eisenberg 2000), but there is strong evidence to suggest that quality of life is also related to factors present within the physical care environment (Parker et al 2004). Although it is difficult to determine the causal attribution between place and care, Moos and Lemke (1980) earlier reported that the workforce who operate in well designed residential settings provide residents with more choice in their daily activities and more influence on operational policies (Parker et al 2004).…”
Section: Care and Support And Building Designmentioning
confidence: 99%